PERSEPSI MASYARAKAT TERHADAP KEBERADAAN RUMAH WALET DI DESA WATUTAU KECAMATAN LORE PEORE KABUPATEN POSOSULAWESI TENGAH - Maksum, Haerani; Rahayu, Ritha; Syukur, Suharno H; Loniyanti, Ni Putu; Ashad, M (SINERGI : Jurnal Riset Ilmiah, 2024)
This research aims to determine the public's perception of the existence of swallow houses in Watutau Village, Lore Peore District, Poso Regency, and the factors that influence people's perceptions of swallow houses. In this research, the population was taken from a community located at a radius of 250 meters, namely 31 heads of families, the number of samples taken was 31 respondents. This research is a qualitative descriptive research. The research method used by the survey method is one of the information collection techniques carried out by compiling a list of questions asked to respondents at the research location. The data analysis used is descriptive statistics using grouping, simplification and presentation of data such as frequency distribution tables and measurements using the likert and chi- square scales. Based on the results of the study, the perception of the community in Watutau Village, Lore Peore District, Poso Regency, is in the category of Disturbed / Disagreed with the exis tence of swallow houses and the most influential factors in the perception of the community in Watutau Village, Lore Peore District, Poso Regency are the distance of houses on sound and socio-cultural indicators on community perceptions.